Discussing deactivation of implantable cardiac defibrillators. (2nd August 2020) - Bahl, Rahul; Dubrey, Simon
Abstract : Implantable cardiac defibrillators are a key component in preventing sudden cardiac death for patients with life-threatening arrhythmias. Through ageing, frailty and the progression of cardiac and non-cardiac morbidity, many will develop a 'life-limiting' condition. This raises the challenge of how to approach making decisions to deactivate the defibrillator function. This article discusses the background to deactivation of implantable cardioverter defibrillators and the practical considerations for different circumstances.